2007
DOI: 10.2337/db07-0378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin Deprivation on Muscle Mitochondrial ATP Production and Gene Transcript Levels in Type 1 Diabetic Subjects

Abstract: OBJECTIVE—Muscle mitochondrial dysfunction occurs in many insulin-resistant states, such as type 2 diabetes, prompting a hypothesis that mitochondrial dysfunction may cause insulin resistance. We determined the impact of insulin deficiency on muscle mitochondrial ATP production by temporarily depriving type 1 diabetic patients of insulin treatment. RESEARCH DESIGN AND METHODS—We withdrew insulin for 8.6 ± 0.6 h in nine C-peptide–negative type 1 diabetic subjects and measured muscle mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 47 publications
6
97
2
1
Order By: Relevance
“…There were no significant differences between control and diabetic participants transcriptional alterations in diabetic myotubes in our study, however, suggests that the downregulation of mitochondrial OXPHOS genes observed in insulin-resistant skeletal muscle in vivo is caused by differences in the magnitude of or response to factors outside the muscle cell, such as neuronal regulation, blood flow and circulating levels of substrates, cytokines and hormones. This idea is supported by several recent studies, which have indicated that both absolute and relative insulinopenia (insulin resistance), hyperglycaemia and circulating levels of NEFA are possible factors contributing to impaired mitochondrial biogenesis in vivo [14,17,18,[32][33][34]. Accordingly, none of the present human studies have been able to prove a cause-and-effect relationship between mitochondrial dysfunction and insulin resistance in vivo [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussioncontrasting
confidence: 38%
“…There were no significant differences between control and diabetic participants transcriptional alterations in diabetic myotubes in our study, however, suggests that the downregulation of mitochondrial OXPHOS genes observed in insulin-resistant skeletal muscle in vivo is caused by differences in the magnitude of or response to factors outside the muscle cell, such as neuronal regulation, blood flow and circulating levels of substrates, cytokines and hormones. This idea is supported by several recent studies, which have indicated that both absolute and relative insulinopenia (insulin resistance), hyperglycaemia and circulating levels of NEFA are possible factors contributing to impaired mitochondrial biogenesis in vivo [14,17,18,[32][33][34]. Accordingly, none of the present human studies have been able to prove a cause-and-effect relationship between mitochondrial dysfunction and insulin resistance in vivo [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussioncontrasting
confidence: 38%
“…5). There is evidence that ROS production may limit respiratory coupling (9) and, thus, efficiency of ATP synthesis; so we speculate that this process may, in part, explain the reduction in ATP production rates reported in insulin-deficient diabetes (18).…”
Section: Discussionmentioning
confidence: 83%
“…This response is attenuated in insulin-resistant T2D individuals, supporting a direct role for insulin resistance leading to mitochondrial dysfunction [143]. Further evidence for this notion comes from a study by Karakelides et al, who showed that acute insulin removal from subjects with type 1 diabetes, caused reductions in mitochondrial ATP production and in mitochondrial gene expression in skeletal muscle [145]. Additionally a recent study in patients with congenital defects in insulin signal transduction, reported that mitochondrial function (assessed by phosphocreatine recovery rates) in muscle was reduced in this population [146].…”
Section: Insulin Resistancementioning
confidence: 82%